VP 2021
DOI: 10.20517/2574-1209.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

The genetic constituent of varicose vein pathogenesis as a key for future treatment option development

Abstract: This perspective focuses primarily on the fundamental part of phlebology, where most attention is paid to the genetic aspects of the pathogenesis of varicose vein disease and where the main breakthrough advances in this area of research are discussed. We propose a direction for further actions to replenish molecular genetic knowledge about the main drivers of pathological processes in varicose vein disease and to complete the creation of an entire picture of pathogenesis, which, in turn, may serve as a key for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…Several studies have been conducted to nd out the genetic association of different genes with VV [18, 19,[28][29][30][31]. In our present study, we found that EFEMP1 gene and its variants play an important role in the pathophysiology of varicose veins.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have been conducted to nd out the genetic association of different genes with VV [18, 19,[28][29][30][31]. In our present study, we found that EFEMP1 gene and its variants play an important role in the pathophysiology of varicose veins.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the significance of a specific genetic variation depends on interactions between one's genotype and environmental factors, with the additional influence of unique epigenetic mechanisms. 58 A multi-ancestry GWAS meta-analysis of 49,765 individuals with varicose veins and over 1 million controls identified 139 risk loci and a genetic overlap between arterial and venous disease. Moreover, it highlighted the pleiotropic effects of obesity and related anthropometric traits on vascular diseases and discovered pathways relevant to varicose vein pathogenesis.…”
Section: Part Ii: Risk Factorsmentioning
confidence: 99%
“…[13]. The pathogenesis of CVD is a very complex multifactorial process, and even a single gene effect can cause little effective influence, and the impact of a particular polymorphism will depend also on genotype-environment interactions, considering also epigenetic mechanisms, which may even be specific to single patients' pathophysiology [14].…”
Section: The Genetic Influencementioning
confidence: 99%